PENDANGAN IGNAZ GOLDZIHER TERHADAP ASAL-USUL MUNCULNYA HADIS NABI MUHAMMAD SAW - M. Dani Habibi; MAHFUD (Journal Khafi : Journal Of Islamic Studies, 2026)
This paper discusses the oriental hadith in outline. We know hadits the second source of Islamic law after the Qur'an is important for Muslims to understand. However, in its development the hadits is understood not only by Muslims but also for non Muslims, especially in the West. Ignaz Goldziher is one of them, he is a western scholar who studied hadith. So that in the end Goldziher concluded that the murini hadith doubts the prophet. Because hadits is used for the benefit of political groups, fiqh and Sufism. Then this triggered Mustofa Azami to criticize Goldziher's conclusion. This article contains qualitative research using literature review. Thus, the researcher focuses on a work by Ignaz Goldziher entitled Muslim Studies.